1980
DOI: 10.1021/bi00543a023
|View full text |Cite
|
Sign up to set email alerts
|

Transfer ribonucleic acid guanine transglycosylase isolated from rat liver

Abstract: Transfer ribonucleic acid (tRNA) guanine transglycosylase (guanine insertion enzyme) was isolated from rat liver and extensively purified. The enzyme catalyzes an exchange of queuine (the base of queuosine, Q) as well as its precursors and guanine for guanine originally located in the first position of the anticodon of "undermodified" tRNATyr, tRNAHis, tRNAAsn, and tRNAAsp from an Escherichia coli mutant or rat ascites hepatoma cells. This is in contrast to the previous observation that E. coli tRNA-guanine tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
70
0
4

Year Published

1982
1982
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 17 publications
0
70
0
4
Order By: Relevance
“…Since 6-thioguanine and 8-azaguanine are both inhibitors of and substrates for tRNA-guanine ribosyltransferase (12,33), we decided to investigate the potential involvement of changes in queuine modification of tRNA in the induction of cell differentiation by these compounds. Figure 2 demonstrates how the queuine content of the tRNA changed in HGPRT-deficient HL-60 cells treated with 6-thioguanine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 6-thioguanine and 8-azaguanine are both inhibitors of and substrates for tRNA-guanine ribosyltransferase (12,33), we decided to investigate the potential involvement of changes in queuine modification of tRNA in the induction of cell differentiation by these compounds. Figure 2 demonstrates how the queuine content of the tRNA changed in HGPRT-deficient HL-60 cells treated with 6-thioguanine.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Ishiguro et al (17) verified that 6-thioguanine itself was capable of inducing the differentiation of HGPRT-deficient HL-60 cells, while wild-type HL-60 cells metabolized the guanine analog to the expected cytotoxic nucleotides. Although these studies demonstrated that 6-thioguanine was the metabolic form responsible for the induction of differentiation of HGPRT-deficient HL-60 cells, the molecular basis for this induction was not established.Many purine analogs, including 6-thioguanine, have been reported to be substrates for the tRNA modification enzyme tRNA-guanine ribosyltransferase (EC 2.4.2.29) (12,33). This enzyme catalyzes the exchange of the highly modified purine analog queuine [7-([3S,4R,5S]-4,5-dihydroxy-2-cyclopent-1-en-3-ylaminomethyl)-7-deazaguanine] for the major base guanine via direct base replacement, whereby the phosphodiester backbone of the tRNA is not broken (1,11,21 obtain this factor from the sera used to supplement the cell culture medium (18,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, they are the only enzymes involved in RNA modification that catalyze the replacement of a genetically encoded base with a highly modified base. Second, there is remarkable correlation of their modified base substrate with their segregation within the primary phylogenetic domains; bacterial TGTs utilize preQ 1 , eukaryotic enzymes utilize queuine (21), and the archaeal enzymes appear to utilize preQ 0 . Finally, their origin in the different domains is associated with disparate tRNA recognition elements.…”
mentioning
confidence: 99%
“…In eukaryotes queuine is inserted into the tRNAs in exchange for guanine by the enzyme queuine: guanine tRNAtransglycosylase [2,3]. Experiments with germ-free mice, fed on queuine-free diet, showed that mice do not synthesize queuine de novo [4,5].…”
Section: Introductionmentioning
confidence: 99%